Management of severe tetanus using magnesium sulfate – The experience in a tertiary health institution in Southern Nigeria - Okike, Clifford O; Muoneke, Uzoamaka V; Ezinne, Okite O; Ezeonwu, Bertilla U; Okolo, Angela A (Indian Journal of Child Health, 2019)
Tetanus is a vaccine-preventable disease caused by the neurotoxin of Clostridium tetani: A motile, Gram-positive, sporeforming obligate anaerobe commonly found in the soil, dust, and alimentary canals of various animals. It remains a public health challenge in the developing countries as the morbidity and mortality rates remain high unlike in the developed world where the incidence is markedly low and no longer contributory to significant mortality. We report two male adolescents admitted in the pediatric department of a tertiary medical center of Nigeria for severe tetanus following an open injury to the limbs. Due to poor response to initial management with the combination of chlorpromazine, phenobarbitone, and diazepam, the latter was replaced with continuous infusion of magnesium sulfate after a loading dose was administered. Both the patients recovered without any prevailing complications and were discharged after 26 and 50 days of hospitalization, respectively, after receiving tetanus toxoid and were subsequently followed up. Successful severe tetanus management without the use of sophisticated medical gadgets and expensive treatment in a resource-poor economy is achievable as demonstrated by our study with the use of magnesium sulfate infusion.